Analysis of an all-in-plane spin-torque oscillator using injection locking to an external microwave magnetic field. (26th April 2021) - Suto, Hirofumi; Sepehri-Amin, Hossein; Asam, Nagarjuna; Zhou, Weinan; Bolyachkin, Anton; Takagishi, Masayuki; Narita, Naoyuki; Tamaru, Shingo; Nakatani, Tomoya; Sakuraba, Yuya
Abstract: We experimentally study the magnetization dynamics of an all-in-plane spin-torque oscillator (AIP-STO) by using injection locking to an external microwave magnetic field. The AIP-STO exhibits multiple frequency signals corresponding not only to the oscillation frequencies of the magnetic layers but also to the difference between these frequencies. The oscillation frequency is identified based on the principle that injection locking occurs only to the signal corresponding to the magnetization oscillation. We also analyze the magnetization dynamics during injection locking by micromagnetic simulations. The results demonstrate that injection locking is a powerful tool for elucidating the oscillation of the AIP-STO.